Bearing behavior of multiple piles for offshore wind driven generator. (1st January 2017) - Lu, Wenjun; Zhang, Ga.; Wang, Aixia
Abstract: Multiple piles have developed rapidly as a foundation for offshore wind-driven generators. A series of model tests employing a centrifuge was conducted to investigate the behavior of the multiple pile foundations of an offshore wind generator. A finite-element analysis model was proposed and confirmed to be effective by the centrifuge model tests. The stiffness of the pile foundation increased with the application of dynamic loading because vibration compacted the soil and decreased its compressibility. The bending moments of the piles exhibited a nearly triangular distribution with an upper peak. The horizontal load caused significant subsidiary axial forces on the multiple piles and accordingly induced significant vertical displacement of the soil. The subsidiary axial force was proportional to the distance between the pile location and load axis. This force generated a resultant bending moment, termed the "general effect", in addition to its own bending moment. The "general effect" played a dominant role in resisting the bending moment induced by the horizontal load. The percentages of the "general effect" of multiple piles were influenced by the pile layout and wind direction. Such the percentage increased with increasing superstructure stiffness, with a tendency toward 100%. Highlights: Coupling of centrifuge and numerical modeling to analysis of bearing mechanism. A prior dynamic loading with small amplitude increased stiffness of foundation. Subsidiary axial force was proportional to distance from pile to load axis. General effect of multiple piles played a dominant role in bearing capacity. Stronger superstructure increased percentage of general effect with tendency to 1.